Peruvian and Latin American trade relations in the context of changes in the international market: the importance of Great Britain and the United States, 1890-1930 - Lobo Collantes, Franco (2020)
This article reconstructs Peruvian foreign trade between 1890 and 1930, classifying it by country, both in imports and in exports separately, using the sources of foreign origin of the most important trading partners: Great Britain and the United States. The article that proposes trade with the United States begins to expand since the early twentieth century, so the context of the First World War accelerates the process. In addition, the low importance of Latin America as a market for manufactures and raw material supplier for the United States and Great Britain, the idea of a dependency relationship between the region and the powers, as well as the concept of informal empire.